'A Struggle for the Soul of the Anglican Church in Wales'. (1st June 2022) - Jones, David
From contemporary speeches, newspaper reportage and the plethora of pamphlets produced, it would be reasonable to conclude that the campaign for disestablishment of the Anglican Church in Wales was essentially a binary struggle between churchmen and their supporters, and Nonconformists. Such a hypothesis would fail to acknowledge the existence of another battle, one for the soul of the Welsh Church. A struggle which was manifested, paradoxically, in the actions and careers of two brothers who both served as senior clergy in the Church: Dean H. T. Edwards and Bishop A. G. Edwards.